Calibration and irradiation study of the BGO background monitor for the BEAST II experiment. (23rd October 2017) - Chen, Y.T.; Lin, J.C.; Chen, J.T.; Chu, K.N.; Huang, K.; Koirala, S.; Liau, J.J.; Lin, F.H.; Lin, K.P.; Shiu, J.G.; Wang, M.Z.
Abstract: Beam commissioning of the SuperKEKB collider began in 2016. The Beam Exorcism for A STable experiment II (BEAST II) project is particularly designed to measure the beam backgrounds around the interaction point of the SuperKEKB collider for the Belle II experiment. We develop a system using bismuth germanium oxide (BGO) crystals with optical fibers connecting to a multianode photomultiplier tube (MAPMT) and a field-programmable gate array (FPGA) embedded readout board for monitoring the real-time beam backgrounds in BEAST II. The overall radiation sensitivity of this system is estimated to be(2.20±0.26)×10^-12 (2.20±0.26)×10 −12 Gy/ADU (analog-to-digital unit) with the standard 10 m fibers for transmission and the MAPMT operating at 700 V. Ourγ γ -ray irradiation study of the BGO system shows that the exposure of BGO crystals to^60 60 Coγ γ -ray doses of 1 krad has led to immediate light output reductions of 25–40%, and the light outputs further drop by 30–45% after the crystals receive doses of 2–4 krad. Our findings agree with those of the previous studies on the radiation hard (RH) BGO crystals grown by the low thermal gradient Czochralski (LTG Cz) technology. The absolute dose from the BGO system is also consistent with the simulation, and is estimated to be about 1.18 times the equivalent dose. These results prove that the BGO system is able to monitor the background dose rate in real time under extreme high radiation conditions. This study concludes that the BGO system is reliable for the beam background study in BEAST II.